Importance of Scar Prevention and Treatment—An Approach From Wound Care Principles. Issue 1 (January 2017) - Marini, Leonardo; Odendaal, Derek; Smirnyi, Sergey
Abstract : BACKGROUND: The increased number of cosmetic surgical and nonsurgical procedures has led to a greater demand to achieve aesthetically acceptable scars. Silicone gel (SG) dressings were evaluated in these cases following the principles of wound care and also minimizing abnormal scar formation. PATIENTS AND METHODS: A newly developed solution in wound care in the form of a SG has proven to be a highly effective treatment for a series of 4 clinically challenging cases presented in this article: postprocedure healing after a laser treatment, nonhealing scalp wounds, chronic relapsing xerotic eczematous cheilitis, and the treatment of scars caused by third degree burns. A standard SG was applied to improve the scar outcome of severe burns of a young child. RESULTS: Silicone gels offer excellent clinical results in these 4 cases. In terms of wound care and scar management, they provide a user friendly, convenient application form and increase patient comfort and compliance. CONCLUSION: To pursue these results, further studies need to be conducted but as of now, there is strong suggestive evidence that SGs indicate beneficial properties for wound care management and scar prevention.